VD_FINDINFO Décision / 2015 / 306 vom 6. März 2015 - VD Tribunal cantonal (2015)
AUDITION DE L'ENFANT, CONFRONTATION, DROIT D'ÊTRE ENTENDU | 141 al. 5 CPP (CH), 154 al. 4 CPP (CH), 393 al. 1 let. a CPP (CH)